The virtual canon: Don Quixote in the spanish cyberland - Dolores Romero López (Texto Digital, 2010)
Could Don Quixote face up to Internet battle? How does a classic that enters into the Network behave on this new and virtual space? Is Don Quixote prepared to fight online? All these questions will be addressed in a research whose first objective is to look for the trail left by the adventures of a Western canon classic. Then we will select some images and texts to analyze how they take part in Web.1 and Web.2. At the end we will assess what literary contents and forms of this canonized novel are still useful for a virtual and global society.